Direct fabrication mechanism of pre-sintered Si3N4 ceramic with ultra-high porosity by laser additive manufacturing. (December 2019) - Wei, Zheng-Hua; Cheng, Li-Jin; Ma, Yi-Xin; Chen, An-Nan; Guo, Xiao-Feng; Wu, Jia-Min; Shi, Yu-Sheng
Abstract: Complex structural Si3 N4 ceramics with ultra-high porosity were innovatively formed by selective laser sintering (SLS) technology without any binder. Due to rapid cooling rate, the high temperature phase constituent and microstructure of the SLSed Si3 N4 poly hollow microspheres (PHMS) were preserved, thus revealing the bonding mechanism of Si3 N4 under the nonequilibrium heat source. Si3 N4 PHMS are bonded by microvilli composed of bamboo-structure SiO2 nanofiber clusters, stacked SiO2 nanospheres and smooth α-Si3.72 N4 nanowires. Finally, the pre-sintered Si3 N4 ceramics with a porosity of 80% are directly fabricated in the atmosphere by SLS, which have the enough strength to satisfy the post-treatment requirements. Graphical abstract: Unlabelled Image